تأثير القصص المصورة التعليمية البهجة لترقية مهارة القراءة لطلاب الصف السابع في مدرسة فركوروان معلمات المتوسطة الإسلامية جومبانج - Mas'ulah, Siti; Naseha, Siti Durotun (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to determine the effect al bahjah comic media to improvement Arabic reading skills student of grade VII at MTSs Perguruan Muallimat Jombang. The research method used is a quantitative approach with a research design only one group pretest posttest, which involves only one group. The research subjects consisted of 26 students grade VII Language I at MTSs Perguruan Muallimat Jombang. Sampling method used is purposive sampling. Data was collected through observation, tests, interviews and documentation. Data analysis used a paired sample t-test. The results of research analysis with the t-test obtained a sig value of 0.000, it is smaller than α, 0.05. And an average score in the pretest 55.85 and 74.00 in posttest, showing an increase of 41,111%. So, the conclucion of learning with al bahjah comic media has a significant effect on improving the reading skills of grade VII students at Madrasah Tsanawiyah Perguruan Muallimat Jombang. Keywords: Media; Comics; Arabic Learning Skill